Participation in Christ: Psalm 118 in Ambrose and Augustine - Boersma, Gerald P. (Augustinianum, 2014)
As bishops, both Augustine and Ambrose wrote sermons on Psalm 118 (119) towards the end of their lives. This article puts these two exegetical works in dialogue with each other by focusing on the common theological theme of participation operative in both commentaries. I argue that both Ambrose and Augustine present a Christological account of participation which functions as the basis of their respective ecclesiologies. Within this overarching Christological framework, the article notes that Ambrose grounds participation in the imago Dei, whereas Augustine’s takes his starting point from the grace Christ offers through the incarnation.